Experimental and numerical investigation of laboratory scale sheetpipe-typed automatic subsurface irrigation - Saptomo, Satyanto Krido; Rudiyanto; Askari, Muhamad; Arif, Chusnul; Suwarno, Willy Bayuardi; Adlan; Rusianto; Setiawan, Budi Indra; Tamura, Koremasa; Matsuda, Hiroshi (Communications in Science and Technology, 2021)
Sheet pipe is a type of perforated pipe used for drainage designed initially for drainage but has the potential for sub-surface irrigation. The objectives of this study were to experiment and observe the performance of the sub-surface irrigation control system with sheet pipe. This investigation covered the observation of water table control and its effect on soil moisture. The detailed process of water flow during the setting of the water table was numerically modeled in 2 dimensions to observe the distribution of soil moisture, soil pressure, and flux. The results showed that the system successfully controlled the water table at the desired level in the experiment. The developed two-dimensional numerical simulation showed the distribution of soil moisture in the model center as a response to the water table increase, represented by the variable head. The soil wetting advances toward soil surface driven by the water table, which was increased gradually and reached saturation at the height of water table setpoint.